ANALYTICAL REVIEW OF JUDICIAL PRACTICE REGARDING THE RECOGNITION OF INDIRECT ACTS DURING PROCEEDINGS IN BANKRUPTCY CASES - Netska, Liubov; Zarudnyi, Nikita (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article: based on an analysis of judicial practice regarding the invalidation of transactions in bankruptcy procedures, identified shortcomings of the relevant legislation in its application by courts, to propose ways to eliminate such shortcomings. Research methods: in the process of scientific research, general scientific (dialectical, formal-logical, methods of analysis and synthesis) and special legal (comparative legal, systemic-structural) methods were used. Results: the peculiarities of the application of the procedure for declaring the debtor’s transactions invalid during bankruptcy proceedings are outlined; identified problems of ambiguous application of the norms of the Code of Ukraine on Bankruptcy Procedures and the Civil Code of Ukraine in their combination when declaring transactions invalid in bankruptcy procedures and proposed ways to eliminate them; the feasibility of ordering a judicial examination in cases of difficulties in determining the market price of property on the date of the transaction in respect of this property has been proven, if such a transaction is declared invalid in the bankruptcy procedure. Discussion: the criteria by which transactions can be declared invalid in bankruptcy procedures are debatable; the grounds for declaring transactions invalid, as set out in Part 2 of Article 42 of the Code of Ukraine on Bankruptcy Procedures, are ambiguous; аpplications for the declaration of invalidity of transactions in bankruptcy proceedings are submitted in accordance with the requirements for a statement of claim under the rules of the Commercial Procedural Code of Ukraine.